2011
DOI: 10.1007/s12562-011-0337-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of a cDNA encoding insulin-like androgenic gland factor from the kuruma prawn Marsupenaeus japonicus and analysis of its expression

Abstract: Androgenic gland hormone (AGH), which is produced in the male-specific androgenic gland (AG) and controls sex differentiation in crustaceans, has been characterized only from isopod species. To date, complementary DNA (cDNA) encoding an androgenic gland-specific polypeptide, which was designated as an insulin-like androgenic gland factor (IAG), has been cloned from three decapod species. IAG has been thought to be a candidate for AGH in decapod crustaceans; however, there has been no clear evidence. To accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…It was shown that the glycosylation affected the peptide conformation of M japonicus IAG . Furthermore, the N ‐glycosylation site is conserved among Penaeidea crustacean IAGs . These observations suggest that the glycan moiety functions to maintain the peptide conformation significant for its activity in these species.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…It was shown that the glycosylation affected the peptide conformation of M japonicus IAG . Furthermore, the N ‐glycosylation site is conserved among Penaeidea crustacean IAGs . These observations suggest that the glycan moiety functions to maintain the peptide conformation significant for its activity in these species.…”
Section: Introductionmentioning
confidence: 94%
“…In addition, the disulfide bond arrangement in A vulgare AGH is not the same as the other insulin‐superfamily peptides, and this irregular disulfide pattern has been shown to be significant for the AGH activity . On the other hand, IAG from a prawn Marsupenaeus japonicus is also a glycopeptide and functions as AGH . It has been reported that the N ‐linked glycan in the B chain of M japonicus IAG is essential for the biological activity, although the glycosylation sites are not conserved among decapod crustacean IAGs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the family Penaeidae, the complete cDNA of IAGs, of the giant tiger prawn Penaeus monodon, the kuruma prawn Marsupenaeus japonicus and the Chinese shrimp Fenneropenaeus chinensis (Li, Li, Sun & Xiang ) have been reported. The definitive demonstration of the AG structure and location by molecular probes has been done in P. monodon and F. chinensis (Banzai, Ishizaka, Asahina, Suitoh, Izumi & Ohira ; Mareddy, Rosen, Thaggard, Manor, Kuballa, Aflalo, Sagi, Paterson & Elizur ; Li et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Our knowledge of the insulin/mTOR pathway in crustaceans and its role in development and growth is fragmentary at best. Insulin-like peptides have been isolated from crustacean tissues (Gallardo et al, 2003;Hatt et al, 1997) and the androgenic gland expresses an insulin-like growth factor that determines male development (Banzai et al, 2011;Manor et al, 2007;Rosen et al, 2010;Sroyraya et al, 2010;. Insulin receptor tyrosine kinases and phosphotyrosyl phosphatases are present in crustacean tissues Chuang and Wang, 1994;Kucharski et al, 1999;Kucharski et al, 2002;Lin et al, 1993).…”
mentioning
confidence: 99%